2002
DOI: 10.1359/jbmr.2002.17.12.2237
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene, Estrogen, and Alendronate Affect the Processes of Fracture Repair Differently in Ovariectomized Rats

Abstract: We investigated the effects of inhibitors of bone resorption (estrogen, raloxifene, and alendronate) on the processes of fracture repair in ovariectomized (OVX) rats. One hundred forty female Sprague-Dawley rats at 3 months of age were either OVX or sham-operated and divided into five groups: sham control, OVX control, estrogen (17␣-ethynyl estradiol [EE2], 0.1 mg/kg), raloxifene (Rlx, 1.0 mg/kg), and alendronate (Aln, 0.01 mg/kg) groups. Treatment began immediately after the surgery. Four weeks postovariectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
160
0
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(185 citation statements)
references
References 42 publications
(73 reference statements)
12
160
0
13
Order By: Relevance
“…Similar positive effects of alendronate have been also reported in the literature. [9][10][11][12][13][14][15][16][17] In addition, plasma calcium levels decreased in the Ovx group, compared to the Shm and alendronate groups with no difference between the Shm and alendronate groups. Iwamoto et al [14] reported decreased plasma osteocalcin and urine deoxypyridinoline levels with increased plasma calcium levels in the Ovx rats.…”
Section: Discussionmentioning
confidence: 88%
“…Similar positive effects of alendronate have been also reported in the literature. [9][10][11][12][13][14][15][16][17] In addition, plasma calcium levels decreased in the Ovx group, compared to the Shm and alendronate groups with no difference between the Shm and alendronate groups. Iwamoto et al [14] reported decreased plasma osteocalcin and urine deoxypyridinoline levels with increased plasma calcium levels in the Ovx rats.…”
Section: Discussionmentioning
confidence: 88%
“…The lack of difference in radiological fracture healing time in our two groups might be partly related to a reduction in hard callus formation, even in the ALN group, compared with that observed in animal studies. 11,[14][15][16] The distal radius was fixed using a locking plate and screws, which provides very stable fixation with angular stability even in osteopenic bone. 37 The amount of callus formation partly depends on the stability of the fracture fragments, 38 with greater callus formation in unstable situations.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, as bisphosphonate is a potent anti-resorptive agent, concerns remain regarding its possible adverse effects on the healing process of fractures. 10,11 Animal experiments consistently demonstrate that bisphosphonate inhibits the remodelling of hard callus to mature lamellar bone, 12,13 although most studies showed no adverse effect on radiologically assessed bony union or the material properties of the already fractured bone. [14][15][16] Human studies on the effect of bisphosphonate administration on the healing of acute fractures have yielded inconsistent results.…”
mentioning
confidence: 99%
“…However, only a few have placed emphasis on the study of fracture healing, a complex cascade of cellular events. Skeletal conditions affect fracture treatment and healing initially but the effects of osteoporosis on this complex process remain unclear, with studies presenting contradictory results (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%